Social Adversity, Sleep Characteristics, and Elevated Blood Pressure Among Young Adult Black Females (Mary Ann Liebert, 2020)
Purpose: We examined whether sleep characteristics and adverse social exposures were associated with elevated blood pressure (BP) in young adult black women. Methods: This is a cross-sectional analysis of existing data from 581 black females who participated in the National Longitudinal Study of Adolescent to Adult Health (Add Health). Adverse social exposures included child abuse, discrimination, perceived stress, social isolation, and subjective social status. Self-reported sleep characteristics were measures of duration, latency, continuity, and snoring. Logistic regression was used to evaluate the influence of social exposures and sleep characteristics on BP. Results: Among the women (mean age=29.1 years), 32.4% had elevated BP (?130 systolic or ?80 diastolic). In adjusted analysis, poor sleep continuity (adjusted odds ratio [aOR]=1.70, 95% confidence interval [CI]=1.07?2.70) and discrimination (aOR=1.61, 95% CI=1.00?2.58) were associated with higher odds of elevated BP, while more social isolation (aOR=0.69, 95% CI=0.48?0.99) was associated with lower odds of elevated BP. Conclusion: Poor sleep continuity and experiencing discrimination may represent key risk factors for hypertension in young black females. Unexpectedly, being more isolated was associated with lower BP. Future research should examine how to adapt current paradigms and measures of social connectedness, isolation, and stress to better elucidate the impact of these factors on the long-term health of young black females.